2006
DOI: 10.1002/jcb.21009
|View full text |Cite
|
Sign up to set email alerts
|

PKC and cAMP positively modulate alkaline‐induced exocytosis in the human mast cell line HMC‐1

Abstract: We study in HMC-1 the activation process, measured as histamine release. We know that ammonium chloride (NH(4)Cl) and ionomycin release histamine, and the modulatory role of drugs targeting protein kinase C (PKC), adenosine 3',5'-cyclic monophosphate (cAMP), tyrosine kinase (TyrK) and phosphatidylinositol 3-kinase (PI3K) on this effect. We used Gö6976 (100 nM) and low concentration of GF 109203X (GF) (50 nM) to inhibit Ca(2+)-dependent PKC isozymes. For Ca(2+)-independent isozymes, we used 500 nM GF and 10 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…Immunoglobulin E (IgE) is an activator of mast cells [5]. The aggregation of IgE receptors (FcεRI) on mast cells triggers complicated biological reactions, such as enhancement of calcium influx, rearrangement of the cytoskeleton, degranulation of prestored granules, and activation of enzymes such as protein kinase C (PKC), cyclooxygenase-2 (COX-2), 5-lipooxygenase (5-LO), and mitogen-activated protein kinases (MAPKs) [6][7][8][9]. After the activation of intracellular signaling pathways, mast cells release various inflammatory mediators, such as prestored histamine and proteases, de novo-synthesized cytokines, chemokines, and eicosanoids, such as prostaglandins and leukotrienes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Immunoglobulin E (IgE) is an activator of mast cells [5]. The aggregation of IgE receptors (FcεRI) on mast cells triggers complicated biological reactions, such as enhancement of calcium influx, rearrangement of the cytoskeleton, degranulation of prestored granules, and activation of enzymes such as protein kinase C (PKC), cyclooxygenase-2 (COX-2), 5-lipooxygenase (5-LO), and mitogen-activated protein kinases (MAPKs) [6][7][8][9]. After the activation of intracellular signaling pathways, mast cells release various inflammatory mediators, such as prestored histamine and proteases, de novo-synthesized cytokines, chemokines, and eicosanoids, such as prostaglandins and leukotrienes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies it was observed that inhibition of PKC-s with rottlerin (5 mM) resulted in a dramatic reduction (or even abolition) of ionomycin-induced Ca 2þ entry in HMC-1 560 cells, as Figure 1A shows [Pernas-Sueiras et al, 2006a]. In the present article it was checked if rottlerin also inhibits thapsigargininduced Ca 2þ entry.…”
Section: Resultsmentioning
confidence: 68%
“…In an earlier work [Pernas-Sueiras et al, 2006a], we reported the striking result of a total ablation of ionomycin-induced calcium increase in HMC-1 560 caused by rottlerin, but this mechanistic effect remains to be explained. In the present study, the rottlerin effects in HMC-1 560 calcium signaling, and the possible differences between ionomycin and thapsigargin-induced calcium entry through SOC channels were investigated.…”
mentioning
confidence: 92%
“…Taking into account that PKC has a central role in mast cell activation and degranulation, these results might indicate some specific role of PKCd in HMC-1 560,816 cell line activation that is not present in the other cell line HMC-1 560 [49,[53][54][55][56]. On the contrary, nuclear PKCd translocation is closely related with cell death in HMC-1 560 cells.…”
Section: Discussionmentioning
confidence: 95%